Tingkat Pengetahuan dan Sikap pada Remaja Putri Tentang Perubahan Fisik Pubertas Pada Siswi SMP Negeri 1 Sukoharjo - Anik Sulistiyanti; Alda Ayu Jifaniata (Jurnal Infokes, 2021)
The physical changes of puberty cause awkwardness for adolescents because they have to adjust to the changes that occur in them. For example, the striking growth of the body, the rapid enlargement of the breasts makes teenagers feel ashamed and excluded from their friends. The results of the preliminary study on October 20, 2020 conducted interviews with 20 students of SMP Negeri 1 Sukoharjo 9 (33.3%), including only knowing the extent of physical changes in puberty and still embarrassed by the changes, 6 (23%) students only knew about puberty, and 5 (20%) students did not know at all about the physical changes of puberty. This study aims to determine the level of knowledge of young girls about the physical changes of puberty at SMP Negeri 1 Sukoharjo. The research design was descriptive quantitative. Samples were all students at SMP Negeri 1 Sukoharjo as many as 83 respondents. Sampling technique is a non probability sampling technique by means of saturated sampling (total sampling). The research instrument was a closed questionnaire using univariate analysis. The results showed the level of knowledge of female adolescents about the physical changes of puberty in SMP Negeri 1 Sukoharjo in good categories as many as 7 students (8.4%), adequate categories as many as 55 students (66.2%), and inadequate categories as many as 21 students (25, 3%. The attitudes of female adolescents about physical changes puberty showed positive attitudes as many as 21 students (25.3%) and negative attitudes as many as 62 students (74.6%)